INTEGRASI-INTERKONEKSI KEILMUAN ALA ABDUL MALIK FADJAR (Refleksi Wacana dan Konstruk Sejarah Pemikiran) - Fiah, Rifda El (Analisis: Jurnal Studi Keislaman, 2011)
This  article  describes  scientific integration  of Abdul  Malik  Fajar’s insight. In essence, discussion surrounding the integration of scientific discourse,  between general/secular  sciences and religious ones, has long been the discussion of experts. The reason why Abdul Malik Fajar’s insight the topic of discussion in this article is because his thoughts on integration  of science not to be simply discourse.  What is more, he was able to pave the way to be an important and esteemed public figure that was pointed to hold the reins of the Minister of Religious Affairs, and followed then to be the Minister of National Education. Reconstruction of Islamic education from dichotomious character into non-dichotomous  one, the existence of the Islamic education  system that should be placed within the framework of sociological purposes, as well as school-based management education as a realization of the decentralization  of education  by offering  school-based  management (SBM) is the most original thought he was offering.